2010
DOI: 10.1007/s10439-010-0217-x
|View full text |Cite
|
Sign up to set email alerts
|

Design of Experiments Approach to Engineer Cell-Secreted Matrices for Directing Osteogenic Differentiation

Abstract: The presentation of extracellular matrix (ECM) proteins provides an opportunity to instruct the phenotype and behavior of responsive cells. Decellularized cell-secreted matrix coatings (DM) represent a biomimetic culture surface that retains the complexity of the natural ECM. Microenvironmental culture conditions alter the composition of these matrices and ultimately the ability of DMs to direct cell fate. We employed a design of experiments (DOE) multivariable analysis approach to determine the effects and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 43 publications
8
85
0
Order By: Relevance
“…Previous studies showed that BDM-ECM obtained by detergent decellularization exhibited high potential for osteogenesis early stages (Hoshiba et al, 2009), but BDM-ECM deposited on biodegradable microfibers surface in a flow perfusion bioreactor and decellularized by freeze/thaw cycles had greater osteogenesis potential at later stages (Liao et al, 2010). Other investigations indicate that complex interactions among several parameters, including cell density and specific culture conditions, may affect the timing of ECM deposition with the highest osteogenesis induction potential (Decaris and Leach, 2011). It is possible that varying degrees of ECM contamination during the different decellularization processes also could contribute to the variability in these results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that BDM-ECM obtained by detergent decellularization exhibited high potential for osteogenesis early stages (Hoshiba et al, 2009), but BDM-ECM deposited on biodegradable microfibers surface in a flow perfusion bioreactor and decellularized by freeze/thaw cycles had greater osteogenesis potential at later stages (Liao et al, 2010). Other investigations indicate that complex interactions among several parameters, including cell density and specific culture conditions, may affect the timing of ECM deposition with the highest osteogenesis induction potential (Decaris and Leach, 2011). It is possible that varying degrees of ECM contamination during the different decellularization processes also could contribute to the variability in these results.…”
Section: Discussionmentioning
confidence: 99%
“…Enzymatic detachment of intact cells by treatment with proteases such as trypsin and collagenase designed to recover viable cells, for example, may damage the remaining ECM and its bound factors. Cell lysis protocols that include treatment with detergent (Decaris and Leach, 2011), alkali (Bass et al, 2007), or freeze/thaw cycles (Deutsch and Guldberg, 2010) can contaminate the remaining ECM with intracellular debris that may negatively affect subsequent cell interaction with the ECM or induce immunological reactions if implanted.…”
Section: Introductionmentioning
confidence: 99%
“…There exists a profound interplay among alternative expansion efforts and progenitor properties. Fluid flow from dynamic 3D culture, for example, enhances ECM deposition [97], which has been shown to preserve progenitor potency [98] or to induce MSCs toward a selected lineage [99]. Furthermore, perfusion culture of MSCs stimulates the synthesis of growth factors including bone morphogenetic protein-2 (BMP-2), FGF-2, TGF-b1, and vascular endothelial growth factor (VEGF) [100].…”
Section: D Expansionmentioning
confidence: 99%
“…The intracellular alkaline phosphatase (ALP) activity was quantified for cells in each medium at each time point and normalized to the DNA content as previously described. 28,29 qPCR analysis of osteogenic markers and LPA receptor expression Total RNA was collected from MSC exposed to SD/H after preconditioning in GM, OM, or OM + (n = 4) using an RNeasy Mini kit (Qiagen, Valencia, CA). About 270 ng of total RNA was reverse transcribed with the QuantiTect Reverse Transcription kit (Qiagen).…”
Section: Biochemical Characterization Of Osteogenic Differentiationmentioning
confidence: 99%